Harnessing Test-Oriented Knowledge Graphs for Enhanced Test Function Recommendation - Liu, Kaiqi; Wu, Ji; Sun, Qing; Yang, Haiyan; Wan, Ruiyuan (Electronics (Basel), 2024)
Application Programming Interfaces (APIs) have become common in contemporary software development. Many automated API recommendation methods have been proposed. However, these methods suffer from a deficit of using domain knowledge, giving rise to challenges like the “cold start” and “semantic gap” problems. Consequently, they are unsuitable for test function recommendation, which recommends test functions for test engineers to implement test cases formed with various test steps. This paper introduces an approach named TOKTER, which recommends test functions leveraging test-oriented knowledge graphs. Such a graph contains domain concepts and their relationships related to the system under test and the test harness, which is constructed from the corpus data of the concerned test project. TOKTER harnesses the semantic associations between test steps (or queries) and test functions by considering literal descriptions, test function parameters, and historical data. We evaluated TOKTER with an industrial dataset and compared it with three state-of-the-art approaches. Results show that TOKTER significantly outperformed the baseline by margins of at least 36.6% in mean average precision (MAP), 19.6% in mean reciprocal rank (MRR), and 1.9% in mean recall (MR) for the top-10 recommendations.